THE EFFECTS OF GENDER, AGE, EYE, AND GROWTH-RELATED FACTORS ON CORNEAL EPITHELIAL AND STROMA THICKNESS IN SCHOOL-AGED-CHILDREN - Kamolovna, Bekmurodova Orzigul (PT. Antis International Publisher, 2024)
Data on corneal epithelium and stroma thickness related to sex, age, eye, and growth parameters of school-age children are limited. In this retrospective study, oct (HUVITZ HOCT-1F, South Korea) corneal epithelial thickness and myopic stroma were measured in 50 men and 60 women (average age 14.12±2.18 years) in the Bukhara region. Regression analysis was used to Decipher the relationship between gender, age, fracture status, axial length, anterior chamber depth, and simple and multiple corneal fracture strength. Age and the thickness of the central angle were positively related to the thickness of the corneal epithelium and negatively related to body weight. In the multiple regression analysis, corneal epithelial thickness was affected by gender and central corneal thickness (CCT), while interstitial thickness was affected by age and gender. The corneal epithelial and stroma thickness was significantly larger in men than in women and was affected by growth. The thickness of the corneal epithelium and stroma was not associated with the severity of myopia, corneal fracture force, or axial length